A sound velocity method for determining isobaric specific heat capacity. Issue 12 (25th September 2022) - Pei, Jun; Li, Hezhang; Zhuang, Hua‐Lu; Dong, Jinfeng; Cai, Bowen; Hu, Haihua; Li, Jing‐Wei; Jiang, Yilin; Su, Bin; Zhao, Li‐Dong; Li, Jing‐Feng
Abstract: Isobaric specific heat capacity ( C p ) is an important parameter not only in physics but also for most materials. Its accurate measurement is particularly critical for performance evaluation of thermoelectric materials, but the experiments by differential scanning calorimetry (DSC) often lead to large uncertainties in the measurements, especially at elevated temperatures. In this study, we propose a simple method to determine C p by measuring the sound velocity ( υ ) based on lattice vibration and expansion theory. The relative standard error of the υ is smaller than 1%, showing good accuracy and repeatability. The calculated C p at elevated temperature (>300 K) increases slightly with increasing temperature due to the lattice expansion, which is more reasonable than the Dulong–Petit value. Abstract : Specific heat capacity can be accurately measured even at elevated temperature by a simple and easy‐to‐implement sound velocity method.